2005
DOI: 10.1007/s00467-004-1798-0
|View full text |Cite
|
Sign up to set email alerts
|

Blood pressure and total peripheral resistance in children with chronic kidney disease

Abstract: We performed a study to assess cardiac output (CO) and total peripheral resistance (TPR) at rest and during peak exercise with the goal to better define the role of these parameters in the development of hypertension in children with chronic kidney disease (CKD) stage 2-4. Fifty-two pediatric patients with CKD (mean age 12.7+/-3.7 years) and 28 healthy individuals of comparable age and sex participated in the study. At rest, children with CKD had a significantly higher systolic and diastolic blood pressure (BP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 9 publications
2
6
0
Order By: Relevance
“…Consistent with the results obtained in animal models, children with stages 2-4 CKD demonstrate increased total peripheral vascular resistance [12]. Similarly, in hypertensive children without CKD but with an average estimated GFR (eGFR) equivalent to renal insufficiency (70.4± 5.4 mL/min per 1.73 m 2 ), significant elevations of ADMA (230%) and SDMA (116%) are observed, as compared to that of normative controls [13].…”
Section: Introductionsupporting
confidence: 81%
“…Consistent with the results obtained in animal models, children with stages 2-4 CKD demonstrate increased total peripheral vascular resistance [12]. Similarly, in hypertensive children without CKD but with an average estimated GFR (eGFR) equivalent to renal insufficiency (70.4± 5.4 mL/min per 1.73 m 2 ), significant elevations of ADMA (230%) and SDMA (116%) are observed, as compared to that of normative controls [13].…”
Section: Introductionsupporting
confidence: 81%
“…This result is in accordance with Matteucci and collaborators that previously observed an increased peripheral resistance in 11 children after renal transplantation [41]. The mechanisms of elevated vascular resistance in chronic kidney diseases could include either increased vasoconstriction or impaired vasodilation [40]. In this regard, increased activity of sympathetic nervous and the Renin Angiotensin System (RAS), elevated levels of endothelin 1 and thromboxane could mediate vasoconstriction while decreased prostacyclin and nitric oxide activity might be responsible for an abnormally reduced vasodilation.…”
Section: Clinical Studiessupporting
confidence: 90%
“…More recently, in an observational study, Mitsnefes and coworkers [40] evaluated the relative role of total peripheral resistance and cardiac output at rest and during peak exercise in the development of hypertension in children at different stages of chronic kidney disease. These authors concluded that increased total peripheral resistance is a major contributor to elevated blood pressure [40]. This result is in accordance with Matteucci and collaborators that previously observed an increased peripheral resistance in 11 children after renal transplantation [41].…”
Section: Clinical Studiesmentioning
confidence: 99%
“…A study of children with CKD stages 2-4 demonstrated that elevated BP was associated with an increase in vascular resistance [20]. They found that children on ACEI or ARB therapy had lower total peripheral resistance suggesting an important role for the renin-angiotensin system.…”
Section: Discussionmentioning
confidence: 99%